1990
DOI: 10.1080/02678299008036753
|View full text |Cite
|
Sign up to set email alerts
|

X-ray investigation of combined main-chain/side-chain liquid-crystalline polymers

Abstract: Structural investigations on six combined liquid-crystalline polymers using the X-ray technique are described. The measurements have allowed a characterization of the liquid-crystalline phases and have led to our first ideas about the phase structures. All mesogenic groups are arranged parallel to each other, the shortest segment in the main-chain or in the side-chain determines the smectic layer spacing. A modified designation for liquid-crystalline phases of high polymers is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Compared with the corresponding main-chain and side-chain LCPs, the mesophase temperature range of MCSCLCPs is surprisingly broad; this is attributed to the synergistic stabilization of the LC phase between the main-chain and side-chain mesogenic units (Endres et al 1990). Later, the synthesis and the correlation between the liquid-crystalline behavior and structural variations of MCSCLCPs have been extensively reported (Watanabe and Tominaga 1993;Reck et al 1989;Diele et al 1990; Kapitza and Zentel 1991;Pakula and Zentel 1991;Ge et al 1997;Piao et al 1997;Chen et al 1999;Ruan et al 2002Ruan et al , 2006Schaefer et al 2006). Traditionally, there are two types of main chain as the backbone of MCSCLCPs: one is non-rigid in character containing flexible spacers (Reck and Ringsdorf 1985;Zentel 1988, 1991;Kremer et al 1989;Poths et al 1991;Zentel and Brehmer 1996;Joo et al 2000;Zhou and Han 2005;Huang and Han 2006) and the other is rigid in nature without any flexible spacers (Ge et al 1997;Piao et al 1997;Lee et al 1999;Cha et al 2001;Ruan et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Compared with the corresponding main-chain and side-chain LCPs, the mesophase temperature range of MCSCLCPs is surprisingly broad; this is attributed to the synergistic stabilization of the LC phase between the main-chain and side-chain mesogenic units (Endres et al 1990). Later, the synthesis and the correlation between the liquid-crystalline behavior and structural variations of MCSCLCPs have been extensively reported (Watanabe and Tominaga 1993;Reck et al 1989;Diele et al 1990; Kapitza and Zentel 1991;Pakula and Zentel 1991;Ge et al 1997;Piao et al 1997;Chen et al 1999;Ruan et al 2002Ruan et al , 2006Schaefer et al 2006). Traditionally, there are two types of main chain as the backbone of MCSCLCPs: one is non-rigid in character containing flexible spacers (Reck and Ringsdorf 1985;Zentel 1988, 1991;Kremer et al 1989;Poths et al 1991;Zentel and Brehmer 1996;Joo et al 2000;Zhou and Han 2005;Huang and Han 2006) and the other is rigid in nature without any flexible spacers (Ge et al 1997;Piao et al 1997;Lee et al 1999;Cha et al 2001;Ruan et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that multiple-step process from smectic to isotropic transitions occurs in combined-type polymalonates having the methoxyazobenzene unit by Ringsdorf et al 2,21 In very recent years, polyketones bearing side-chain azobenzene unit were disclosed to Relationships between Structures and Liquid Crystalline and Optical Properties in Combined-type Copolyisophthalates form smectic LC phase. 29 In this way, many sidechain or combined-type polymers having the azobenzene moieties exhibit smectic phases.…”
Section: Mesomorphic Propertiesmentioning
confidence: 99%
“…2, 21 Kodaira et al disclosed that copolymalonates with the sidechain nitroazobenzene and methoxybiphenyl units have wider temperature ranges of nematic phase than the homopolymalonates, where electron donor-acceptor interaction between the mesogens with electron-donating and electron-withdrawing groups acts an important role. 22 In addition, copolymers containing monomer units with specific interaction such the electron donor-acceptor interaction have been found to form smectic mesophases.…”
mentioning
confidence: 99%
“…These polymers are commonly called main chain liquid crystalline polymers (LCPs). [1][2][3][4][5][6][7] In contrast, the side chain LCPs [8][9][10][11][12][13] contain the mesogenic units in the side branches or as pendants. Many papers [1][2][3][4][5][6][7] have been published during the past quarter of a century on the structure-property relationships of main chain LCPs.…”
Section: Introductionmentioning
confidence: 99%